Adverse Drug Reactions Among Patients Enrolled in an Outpatient Parenteral Antimicrobial Therapy (OPAT) Program 2015–2016 at UNC Medical Center. (4th October 2017) - Chundi, Vahini; Eichholz, Anh; Nwankwo, Onyeka; Kinlaw, Alan; Kufel, Wesley; Medlin, Tenesha; Fletcher, Lisa; Marx, Ashley; Farel, Claire
Abstract: Background: The UNC Medical Center OPAT program was started in 2015 to provide multidisciplinary monitoring and management of patients discharged on parenteral antimicrobials. We examined characteristics of incident adverse drug reactions (ADRs) observed in our initial cohort of OPAT patients. Methods: We abstracted electronic health records for the first 250 patients enrolled in the OPAT program. 223 patients with sufficient recorded data for entire OPAT course were included in the analysis. ADRs meeting criteria as detailed in Table 1 were collected and further stratified by antimicrobial regimen. Results: 57 patients (26%) experienced at least one ADR during OPAT therapy. The frequency of specific ADRs associated with OPAT therapies are provided in Figure 1. Β-lactam regimens were most frequently associated with liver dysfunction, while combinations of β-lactams and vancomycin were associated with kidney dysfunction. Median days on OPAT regimen was 19 days (IQR: 10–29) for patients who experienced an ADR compared with 39 (IQR: 30–44) for patients who did not experience an ADR. Conclusion: ADRs were most commonly observed within the first three weeks of therapy, particularly for patients receiving vancomycin and a β-lactam antimicrobial in combination. These results underscore the critical role of a multidisciplinary team in providing laboratory monitoring and response to abnormal results for OPAT patients. In addition, closer monitoring within the first three weeks of therapy may provide opportunities for regimen changes or dose adjustment to avoid toxicities. Disclosures: All authors: No reported disclosures.